Sistem Pendukung Keputusan Pemilihan Perguruan Tinggi Swasta Terbaik Menggunakan Metode VIKOR - Sitorus, Khoirul Pahotan (Journal Global Technology Computer, 2024)
Coordination of Private Universities abbreviated as Kopertis is an institution formed by the government that is tasked with providing guidance to private universities in its working area. Coordination of Private Universities I or abbreviated as Kopertis Region I is a division of the Kopertis working area which covers the province of North Sumatra. The problem faced by Kopertis Region I North Sumatra is that it is difficult to assess every private university in North Sumatra because the distance between one private university and another private university is far apart so that the Kopertis is difficult to reach and sometimes the reports received do not match reality and not all of them can be objectively assessed because some private universities have a long distance from North Sumatra, so sometimes in the selection of the best private universities it is not assessed as a whole. Decision Support System is an interactive information system that provides modeling, information, and data manipulation. A Decision Support System can also be defined as a computer system that manages data into information to make decisions from specific semi-structured problems. Decision Support Systems aim for a decision that requires decision judgment that cannot be supported by algorithms at all or to help make decisions in semi-structured situations and unstructured situations, where no one knows exactly how the decision should be designed. The vikor method is a method to determine the ranking of existing samples by looking at the results of the utility value, regression and solution distance as the best alternative from each sample. The vikor method focuses on ranking and selecting from a set of alternatives, and determining a compromise solution for conflicting criteria problems, which can help decision makers to reach a final decision.